الاخفاقات المعرفية وعلاقتها بالإدمان الرقمي لدى طلبة كلية التربية للعلوم الانسانية جامعة واسط - رضا عبد السيد المكصوصي ضرغام (Journal of College of Education, 2019)
The Objectives of the present study. The present study aims to identify: The level of cognitive failure and digital addiction among the students of the Faculty of Education for Human Sciences. level of differences according to gender variables and specialty cognitive failure and digital addiction among students of the Faculty of Education for human sciences. the correlation relationship with statistical significance between both the cognitive failure and digital addiction of students. Community and model. The community of the present study consists of students from the university of Wassit for the academic year (2018/2019), morning studies, males and females, scientific and humanities. The tools. The researcher has used the following tool after confirming its validity for measurement through the calculation of its validity and stability using the appropriate methods and procedures: Measurement of cognitive failure. The researcher adopted the scale (Rkabi, 2010) consists of (50) paragraph: Digital addiction measurement. The researcher adopted the scale (increase, 2017) consists of (20) paragraph: Statistical methods: The researcher has used the statistical program (Spss) in the analysis of the results of the present study. The researcher has adopted the statistical tests that fit with the objectives of the present study: descriptive statistics, the test of one sample, Kay square test, and analysis of binary contrast without. The results: The results of statistical analysis using the statistical program (Spss) have resulted in the following results: They have a high degree of cognitive failure 2- The students of the Faculty of Education for Human Sciences possess high levels of digital addiction 3 - There are differences in favor of males in the digital addiction and cognitive failure of students of the Faculty of Education for Human Sciences Wasit University. 4- There is a correlation between the cognitive failure and digital addiction among the students of the Faculty of Education for Human Sciences.